2021
DOI: 10.4081/gh.2021.961
|View full text |Cite
|
Sign up to set email alerts
|

Spatial cluster analysis of COVID-19 in Malaysia (Mar-Sep, 2020)

Abstract: Coronavirus disease 2019 (COVID-19) is the current worldwide pandemic as declared by the World Health Organization (WHO) in March 2020. Being part of the ongoing global pandemic, Malaysia has recorded a total of 8639 COVID-19 cases and 121 deaths as of 30th June 2020. This study aims to detect spatial clusters of COVID-19 in Malaysia using the Spatial Scan Statistic (SaTScan™) to guide control authorities on prioritizing locations for targeted interventions. The spatial analyses were conducted on a monthly bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…A retrospective spatial scan study in Southeast Asia during January 13, 2020 and March 16, 2020 further confirmed that Malaysia and Singapore were the most likely cluster between March 4-March 16, 2020 (RR = 72.07, LLR = 1910.08, p < 0.001) (44). The most likely cluster for the period 2 (January 25 to October 8, 2020) consisted of Negeri Sembilan, Putrajaya, Kuala Lumpur, and Selangor (10 districts) in this study correlates with a state-level spatial scan analysis study in Malaysia (45).…”
Section: Discussionsupporting
confidence: 88%
“…A retrospective spatial scan study in Southeast Asia during January 13, 2020 and March 16, 2020 further confirmed that Malaysia and Singapore were the most likely cluster between March 4-March 16, 2020 (RR = 72.07, LLR = 1910.08, p < 0.001) (44). The most likely cluster for the period 2 (January 25 to October 8, 2020) consisted of Negeri Sembilan, Putrajaya, Kuala Lumpur, and Selangor (10 districts) in this study correlates with a state-level spatial scan analysis study in Malaysia (45).…”
Section: Discussionsupporting
confidence: 88%
“…Also, this study is based on large population-based data from an NCI SEER program cancer registry that meets the high-quality standards. Furthermore, SaTScan spatial analysis used in identifying geographic clusters is a free globally used cluster-detecting epidemiologic tool for identifying spatial clusters of infectious and chronic diseases, including COVID-19, malaria, cancers, and others …”
Section: Discussionmentioning
confidence: 99%
“…24,[45][46][47][48][49][50][51][52][53][54] Figure 2. Census Tract-Level Characteristics of Patients With Late-Stage Cervical Cancer in Texas, 2014-2018 by Cluster Classification Bar chart showing the characteristics of census tracts containing late-stage cervical cancer cases stratified by cluster classification (hot spots, cold spots, rest of Texas).…”
mentioning
confidence: 99%
“…It can provide public health authorities with important information about the pandemic to enable better management under the situation [8][9][10]. Among diverse spatiotemporal methods, space-time scanning is one of the most popular methods adopted by many studies to explore spatiotemporal clusters in different regions worldwide, such as Mainland China [11], the United States [12], Mexico [13], Spain [14], Malaysia [15], Bangladesh [16], Brazil [17], and South Korea [18]. In SEA, previous studies have applied this analysis to investigate the first wave of COVID-19 cases [19,20].…”
Section: Introductionmentioning
confidence: 99%